Laboratorial and physiological validation of comercial kits for quantification of fecal corticoids of captive chimpanzees (Pan troglodytes) and orangutangs (Pongo pygmaeus) under environmental enriched conditions - Pizzutto, Cristiane Schilbach; Sgai, Manuela Gonçalves Fraga Geronymo; Viau, Priscila; Chelini, Marie Odile Monier; Oliveira, Cláudio Alvarenga de; Guimarães, Marcelo Alcindo de Barros Vaz (Brazilian Journal of Veterinary Research and Animal Science, 2008)
A comparative study of fecal corticoids (FC) concentrations was carried out with chimpanzees (Pan troglodytes) e orangutans (Pongo pygmaeus). Fecal samples were collected before (Basal) and just after (Habituation) enrichment introduction and analyzed. We performed biochemical and physiological validations of the ImmunuChemTM Double Antibody Corticosterone kit for radioimmunoassay from MP Biomedicals for quantifying FC concentrations. To establish the biochemical validity of our assay we performed parallelism assays in which pooled fecal extracts from both species were spiked with known quantities of corticosterone standard and the slopes of the curves obtained with these samples and the standard curves of the kits were compared.The correlation coefficients were R^2=0.98 (Y= 17.23+1.31*X) for chimpanzees and R^2=0.99 (Y=11.14+1.29*X) for orangutans. For biological validation, we used the introduction of environmental enrichment to trigger a rise in FC levels as a consequence of the response to a stressor. Concentrations were expressed as mean and SEM. Mean concentrations of fecal corticosteroids were: Basal: 5.90 ± 2.41 x10³ ng/g of feces, Habituation: 14.92± 4.66 x10³ ng/g of feces for chimpanzees and Basal: 91.1 ± 30.0 x10³ ng/g of feces, Habituation: 185.1 ± 57 x10³ ng/g of feces for orangutans. For both species, the mean concentrations of Basal and Habituation periods were significantly different.